The effects of nalmefene on emotion processing in alcohol use disorder - A randomized, controlled fMRI study - Vollstädt-Klein, Sabine; Bumb, Jan Malte; Dinter, Christina; Karl, Damian; Koopmann, Anne; Hermann, Derik; Kiefer, Falk (European neuropsychopharmacology, 2019)
Nalmefene is a µ- and δ-opioid receptor antagonist and a partial κ-opioid receptor agonist. The drug is suggested to reduce the craving for, and the consumption of alcohol effectively, also alleviating anxiety and anhedonia. The present fMRI study is the first to investigate the processing of emotions as a possible mechanism of action of nalmefene in humans. Fifteen non-treatment-seeking participants suffering from alcohol use disorder (AUD) (24-66 years; 5 females) finished this randomized, placebo controlled, double blind study. Following a cross over design, participants received either a single dose nalmefene or a placebo, with an interval of one week between sessions. Using fMRI, we investigated neural reactivity during the presentation of emotional faces picture sets. Additionally, we performed a visual dot-probe task to detect nalmefene's effects on attentional bias. We detected an increase in the response to emotional faces in the supramarginal gyrus, the angular gyrus as well as the putamen in the nalmefene vs. placebo condition. However, contradictory to our initial hypotheses, amygdala activation was not altered significantly in the placebo condition - a limitation, which might be associated with a lack of activation in the placebo condition maybe due to the small sample size. Attentional bias analyses revealed an interaction effect by trend, which was driven by a significant effect in a sub-analysis showing increased attentional shift towards happy compared to fearful facial expressions under nalmefene. Nalmefene increased brain activation in areas responsible for empathy, social cognition and behavior, which might help alleviating the reinforcing properties of alcohol.